Pediatric laparoscopy and adaptive oxygenation and hemodynamic changes - Gloria Pelizzo; Veronica Carlini; Giulio Iacob; Noemi Pasqua; Giuseppe Maggio; Marco Brunero; Simonetta Mencherini; Annalisa De Silvestri; Valeria Calcaterra (MDPI AG, 2017)
Adaptive changes in oxygenation and hemodynamics are evaluated during pediatric laparoscopy. The children underwent laparoscopy (LAP Group, n=20) or open surgery (Open Group, n=10). Regional cerebral (rScO2) and peripheral oxygen saturation (SpO2), heart rate (HR), diastolic (DP) and systolic pressure (SP) were monitored at different intervals: basal (T0); anesthesia induction (T1); CO2PP insufflation (T2); surgery (T3); CO2PP cessation (T4); before extubation (T5). At T1, in both the LAP and Open groups significant changes in rScO2, DP and SP were recorded compared with T0; a decrease in SatO2 was also observed at T5. In the LAP group, at T2, changes in HR related to CO2PP pressure and in DP and SP related to IAP were noted; at T4, a SP change associated with CO2PP desufflation was recorded. Open group, at T3 and T5 showed lower rScO2 values compared with T1. Pneuperitoneum and anesthesia are influent to induce hemodynamics changes during laparoscopy.